Passive vs. active warm-up combined with stretching on hamstring flexibility and maximal voluntary contractions - Marion Hitier; Denis Cesar Leite Vieira; Carole Cometti; João Luiz Quagliotti Durigan; Nicolas Babault (PLoS ONE, 2025)
This study aimed to compare the effects of passive and active warm-up protocols combined with static or neurodynamic stretching on hamstring muscle function. Sixteen individuals (7 men and 9 women) performed three experimental sessions in a randomized order: 1) passive warm-up and static stretching, 2) passive warm-up and neurodynamic stretching, 3) active warm-up and static stretching (control condition). Passive warm- up consisted of 20 minutes in a 45°C hot-room. Active warm-up included 10 minutes of cycling and 10 minutes of sub-maximal contractions. Following warm-up, the participants were engaged in six sets of 30-second stretches, either performed using static or neurodynamic modalities. Testing involved two maximal voluntary contractions (MVC), a passive knee extension test (to evaluate range of motion and hamstring stiffness), and a stand-and-reach test (used for flexibility assessment) conducted before, after warm-up, and after stretching. Electromyography from the biceps femoris and semitendinosus were recorded during MVC. Results revealed a significant time effect for flexibility (p < 0.001). Flexibility enhancements were obtained following active and passive warm-ups and further increased after the stretch, independently of the stretch intervention. The electromyographic activity of the semitendinosus muscle was affected by the time (p = 0.004). It revealed a decrease after stretching as compared to a post-warm-up measurement. No other differences were observed between conditions and time for maximal torque and stiffness indexes. It is concluded that both the active and passive warm-up methods are efficient to increase flexibility. Irrespective of the modality, stretching further improved flexibility without any alteration in muscle viscoelastic properties.